1999
DOI: 10.1180/minmag.1999.063.6.08
|View full text |Cite
|
Sign up to set email alerts
|

Pumpellyite from the oceanic crust, DSDP/ODP Hole 504B

Abstract: Pumpellyite has been found in doleritic basalt of a sheeted dyke complex drilled from 2072.1 m below sea floor in DSDP/ODP Hole 504B, south of the Costa Rica Rift, eastern Pacific. It occurs as finegrained crystal aggregates accompanied by albite, chlorite and chalcopyrite, which partially replace a plagioclase phenocryst (An85-88) that is also associated with primary magnetite. Chemical compositions of the pumpellyite vary antithetically in relation to Fe* and A1 as well as Fe* and Mg, indicating the dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Hyaloclastite clasts display pumpellyite aggregates in an assemblage of chlorite and quartz. Similar assemblages have been described in hydrothermally altered oceanic basalts [e.g., M evel, 1981; Ishizuka, 1999] and ascribed to seawater/rock interactions at temperatures consistent with prehnite-pumpellyite conditions (at 2508C), which are somewhat cooler than greenschist conditions. The remaining three breccias show textures that are not clearly fault-related, and are referred to as undetermined in Table 2 (see also Figure 1b).…”
Section: Deformed Samples From the Detachment Rubble Blanketsupporting
confidence: 74%
“…Hyaloclastite clasts display pumpellyite aggregates in an assemblage of chlorite and quartz. Similar assemblages have been described in hydrothermally altered oceanic basalts [e.g., M evel, 1981; Ishizuka, 1999] and ascribed to seawater/rock interactions at temperatures consistent with prehnite-pumpellyite conditions (at 2508C), which are somewhat cooler than greenschist conditions. The remaining three breccias show textures that are not clearly fault-related, and are referred to as undetermined in Table 2 (see also Figure 1b).…”
Section: Deformed Samples From the Detachment Rubble Blanketsupporting
confidence: 74%
“…The presence of pumpellyite (rather uncommon in the oceanic environment; Me´vel, 1981), in corona with chlorite and goethite around chalcopyrite in a calcitebearing gabbro also suggest a low-temperature, fluidcontrolled, hydrothermal reaction. The same feature has been observed by Ishizuka (1999): the pumpellyite and the associated chlorite and goethite are the products of the reaction between plagioclase and an iron oxide with a fluid bringing Cu and S.…”
Section: Origin and Evolution Of Paragenesessupporting
confidence: 72%
“…It was also observed that basalts displaying the mineralogical assemblages characteristic of the prehnite-pumpellyite facies were rarely found in the seafloor, but were more frequent in ophiolites. Prehnite alone is common in oceanic metagabbros (e.g., [78,129]), but pumpellyite has only been observed three times in ocean-floor metabasalts [93,120,128]. Pumpellyite was associated with prehnite in two of these three oceanic occurrences.…”
Section: Misusing Eskola's Concept Of Metamorphic Faciesmentioning
confidence: 99%